Dança Nordestina de Santino Parpinelli: aspectos históricos analíticos e interpretativos - Paulo Andre de Souza Nascimento (2005)
It focus the work Dança Nordestina composed for violinist, educator, and composer Santino Parpinelli (1912-1991). Despite of this composition is one of the most known of the Brazilian double bass repertory and, probably, one that has more versions and arrangements, the composer isnt well known. With the purpose of to context of thework and to evidence of Parpinellis importance for national repertory, it approaches aspects of composers biography, and the dissemination of this work made for the double bassist Sandrino Santoro, to whom Dança Nordestina was dedicated. It trends to show how Parpinelli composed Dança Nordestina from musical elements of the Northeastern native tradition, specially of the baião, and suggests procedures anddecisions of interpretation for this work, from melodies characteristics (intervals and rhythmics) and harmonics, aiming to give subsidies for a quality performance to the performer and to the teacher. The methodological procedures include a review of literature about popular musical genres of the Brazilian Northeastern; a analysis of works form; the identification of characteristics elements of baião (scales, melodies,and rhythmics) and of other references of the Northeastern music, like the cantoriaand the repente, presents in the work; verification and discussion about dynamics and articulations inconsistencies in the work; and discussion and presentation of suggestions of articulations and bowings for the performance of the work. Include scores and records of the principal versions of Dança Nordestina.